The Effect of TGF-β on Treg Cells in Adverse Pregnancy Outcome upon Toxoplasma gondii Infection - Zhao, Mingdong; Zhang, Haixia; Liu, Xianbing; Jiang, Yuzhu; Ren, Liqin; Hu, Xuemei (Frontiers in Microbiology, 2017)
Toxoplasma gondii (T. gondii) is a ubiquitous intracellular protozoan parasite that causes adverse pregnancy outcomes. Its infection downregulates the Treg cell population and TGF-β level, which may contribute to adverse pregnancy outcomes. TGF-β plays a critical role in Treg cell development, but whether TGF-β treatment can affect the number and function of Treg cells and hence alleviate adverse pregnancy outcomes caused by T. gondii infection remains elusive. In this study, T. gondii-infected pregnant mice were treated with TGF-β or TGF-β-neutralizing antibody. The pregnancy outcomes were observed on gestational day 14. The numbers of Treg cells and pSmad3, PD-1, and CTLA-4 expression of Treg cells were analyzed by flow cytometry. Histological changes were assessed using HE staining, while IL-10 and TNF-α levels were measured using ELISA. The results indicated that TGF-β treatment improved the T. gondii-induced adverse pregnancy outcomes, with alleviation of hemorrhage, restoration of uterine spiral arteries of the placenta, and increased Treg cell numbers; meanwhile, TGF-β neutralization resulted in more serious adverse pregnancy outcomes, with serious hemorrhage, more dilated uterine spiral arteries, and decreased Treg cell numbers. pSmad3 expression in CD4+ cells and CTLA-4 and PD-1 levels on Treg cells were upregulated by TGF-β treatment, but downregulated by TGF-β neutralization. The ratio of IL-10/TNF-α also increased after TGF-β treatment, but decreased after TGF-β neutralization. Our data indicate that TGF-β treatment could improve adverse pregnancy outcomes caused by T. gondii infection by upregulating Treg cell differentiation and function via the TGF-β/Smad3 signaling pathway, but not the proliferation of Treg cells.